2023
DOI: 10.1002/fsn3.3354
|View full text |Cite
|
Sign up to set email alerts
|

Mycoprotein as chicken meat substitute in nugget formulation: Physicochemical and sensorial characterization

Abstract: The aim of this study was to replace chicken breast by mycoprotein in nuggets and optimizing the sensory and technological properties. In the first step of the study, 14 formulations were prepared by mixture design to evaluate the impact of three binding agents (as independent variables): soy protein isolate, phosphate, and carrageenan on sensory properties. Then, the optimized formulation of mycoprotein nugget (with higher acceptability) was characterized and compared to chicken nugget (control) from texture,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The harvested biomass is subjected to additional processing steps to enhance its textural and sensory attributes. 24 The resulting mycoprotein is then harnessed as a versatile ingredient in diverse food applications, effectively substituting conventional meat sources. This comprehensive process underscores the potential of submerged fermentation as a proficient route for mycoprotein production, albeit with considerations of energy demand due to the requisite liquid medium and agitation.…”
Section: Methods Of Productionmentioning
confidence: 99%
“…The harvested biomass is subjected to additional processing steps to enhance its textural and sensory attributes. 24 The resulting mycoprotein is then harnessed as a versatile ingredient in diverse food applications, effectively substituting conventional meat sources. This comprehensive process underscores the potential of submerged fermentation as a proficient route for mycoprotein production, albeit with considerations of energy demand due to the requisite liquid medium and agitation.…”
Section: Methods Of Productionmentioning
confidence: 99%
“…Beet root extract (0.2%, w/w) enhanced the color of a mushroom-based minced meat substitute, both fresh and cooked (Mazumder et al, 2023). Contrary to the need for colorants, Hashempour-Baltork et al (2023) reported that using mycoprotein increased the redness of chicken nuggets formulated with carrageenan. Moreover, it was suggested that white pepper can be used to modulate the lightness of the product.…”
Section: Natural Colorantsmentioning
confidence: 99%
“…Mycoprotein pastes are often described as light in color. Therefore, the addition of spices and colorants is important to simulate the heme color of conventional meat ( Hashempour-Baltork et al, 2023 ).…”
Section: Novel Foods and Their Colorsmentioning
confidence: 99%
“…Fungal single-cell proteins can serve as a direct source for producing meat alternatives, and the recombinant proteins produced by fungi can be employed as technical additives in the production of meat substitutes [ 7 , 8 ]. For example, mycoprotein from Fusarium venenatum was used instead of chicken breast tissue to make chicken nuggets [ 9 ], the filamentous fungus Aspergillus oryzae was employed for the production of hamburger patties [ 10 ], and S. cerevisiae -derived exogenous cytokines were used to promote the growth of porcine muscle satellite cells (MuSCs) for cultured meat production [ 7 ]. In summary, microbial proteins represent a dominant paradigm for future protein manufacture.…”
Section: Introductionmentioning
confidence: 99%